Fibrinogen: A Marker in Predicting Diabetic Foot Ulcer Severity - X. H. Li; L. Y. Guan; H. Y. Lin; S. H. Wang; Y. Q. Cao; X. Y. Jiang; Y. B. Wang (Journal of Diabetes Research)
Aims. To examine whether fibrinogen levels are a valuable biomarker for assessing disease severity and monitoring disease progression in patients with diabetic foot ulcer (DFU). Methods. A retrospective study was designed to examine the utility of fibrinogen in estimating disease severity in patients with DFU admitted to our hospital between January 2015 and January 2016. In total, 152 patients with DFU were enrolled in the study group, and 52 age and gender matched people with diabetes but no DFU were included as the control group. DFU severity was assessed using Wagner criteria. Results. Patients with DFU were divided into 2 subgroups based on the Wagner criteria. Mean fibrinogen values were significantly higher in patients with DFU grade ≧ 3 compared to those with DFU grades 1-2 (5.23 ± 1.37 g/L versus 3.61 ± 1.04 g/L). Using ROC statistic, a cut-off value of 5.13 g/L indicated the possible amputation with a sensitivity of 81.8% and a specificity of 78.9% (positive predictive value [PPV] 78.6%, negative predictive value [89.0%]). Fibrinogen values were found to be correlated with CRP levels, neutrophil, and WBC count. Conclusions. Fibrinogen levels might be a valuable tool for assessing the disease severity and monitoring the disease progression in patients with DFU.